Implementasi Terapi Relaksasi Otot Progresif Untuk Mengatasi Ketidakstabilan Kadar Glukosa Darah - Egidia Yusra Thunggal; Nining Indrawati (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2023)
Background of StudyDiabetes mellitus (DM) is a collection of symptoms in a person caused by an increase in blood glucose levels due to a progressive decrease in insulin secretion by insulin resistance. Non-pharmacological therapy that can be used for patients with diabetes mellitus in controlling blood glucose levels is one of them with progressive muscle relaxation therapyMethods : The writing of this scientific paper uses a descriptive method in the form of a study. Sampling was carried out using a purposive sampling technique with a sample of 1 personResults : A case study conducted on Bp. S with a diagnosis of diabetes mellitus and the main symptoms that appear are body weakness, headache and GDS 784mg/dL. The results showed that progressive muscle relaxation therapy was carried out for two days twice a day, on the first day before the intervention, blood glucose levels were 278mg/dL and after blood glucose levels were 277mg/dL, on the second day before the intervention, blood glucose levels were 299mg. /dL after intervention blood glucose levels 290mg/dL.Conclusion : This case study shows that progressive muscle relaxation in patients with diabetes mellitus can reduce blood glucose levels.Keywords : Progressive Muscle Relaxation, Diabetes Mellitus, Blood Glucose Level